STRATEGI KOMUNIKASI PRAJURU DALAM MEMILIH PRAWAYAH DI DESA ADAT TIMBRAH KABUPATEN KARANGASEM - I Made Bagiarta Mandraguna; I Gusti Ngurah Sudiana; Ida Bagus Gede Candrawan (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2023)
ABSTRACT Prajuru Timbrah Traditional Village has difficulty choosing prawayah. This obstacle made prajuru have to carry out a communication strategy. How this communication strategy is carried out in selecting interesting prawayah for further research. This thesis research takes the title "Prajuru Communication Strategy in Choosing Prawayah in Timbrah Traditional Village". The formulation of the problem, among others; 1) What is the Timbrah Traditional Village Prajuru communication strategy in choosing prawayah? 2) What are the obstacles and solutions to the Timbrah Traditional Village Prajuru communication strategy in choosing prawayah? 3) What is manifested in the Timbrah Traditional Village Prajuru communication strategy after being able to choose prawayah during religious ceremonies in the Timbrah Traditional Village? The theories used in this study are Role Theory, Social Penetration Theory and SMCR (Source-Message-Channel-Receiver) Theory. This study uses a qualitative approach. This type of data collection is qualitative from primary and secondary data sources. Data collection techniques, namely observation, interviews, documentation. The findings of the research results are prajuru communication strategies in choosing prawayah, carried out by applying communication methods in several forms, including informative, coercive and educative. Obstacles in implementing the communication strategy, occur internally and externally. Meanwhile, solutions for internal obstacles are overcome by making decisions directly in the prajuru internal procession, to implementing Awig-awig in a straightforward and firm manner. Furthermore, external obstacles, the solution is to return to educating the public about the importance of the existence of prawayah. The effort to choose prawayah with katepak widhi is also considered as one of education. The implications of this communication strategy, have a positive or negative impact. The positive impact is that filling in the prawayah is filled again, selecting the next prawayah becomes easier, the implementation of religious ceremonies in the Timbrah Traditional Village becomes smoother. Residents' awareness is also growing towards the importance of the existence of prawayah. The negative impact is that prajuru do not get the ideal human resources to become prawayah. The adaptation process as prawayah is relatively longer, because you have to start from scratch. The level of public trust and confidence in prawayah as the leader of religious rituals and the enlightener of the people has decreased. Keywords: Communication Strategy, Prajuru, Prawayah